Dietary caffeine and its negative link to serum Klotho concentrations: evidence from the National Health and Nutrition Examination Survey - Wu, Haimeng; Lu, Ping (Frontiers in Nutrition, 2024)
BackgroundThis is the initial investigation assessing the association between caffeine consumption through diet and circulating Klotho concentrations, with Klotho being recognized as a key biomarker of healthspan and aging.MethodsThis cross-sectional analysis utilized data from 11,169 adults who participated in the National Health and Nutrition Examination Survey (NHANES). Caffeine consumption was evaluated using 24-h dietary recall interviews by trained professionals, and serum Klotho concentrations were measured via an enzyme-linked immunosorbent assay (ELISA). Generalized linear models and threshold effect analysis were employed to examine the relationship between caffeine intake and serum Klotho concentrations. Interaction tests and subgroup analyses were conducted to identify potential effect modifiers.ResultsAfter controlling for covariates, a negative correlation was observed between dietary caffeine consumption and serum Klotho concentrations, with each additional 100 mg of dietary caffeine consumption, Klotho decreased by 3.40 pg./mL (95% confidence interval [CI]: −5.73, −1.07). Participants in the fourth quartile of dietary caffeine consumption showed a 23.00 pg./mL reduction in serum Klotho concentrations (95% CI: −39.41, −6.58) compared to individuals in the first quartile. Threshold effect analysis revealed a threshold point corresponding to natural log-transformed caffeine value >3.74 (equivalent to ~41 mg/day), above which Klotho levels demonstrated a more pronounced decline. Subgroup analyses indicated that this association was more significant in participants with sedentary activity >480 min and without hypertension.ConclusionOur study reveals a significant, dose-dependent negative association linking caffeine intake with serum Klotho concentrations in the United States adults aged 40–79 years, with potential thresholds beyond which the effects become more pronounced. Additional studies are required to verify these results and investigate the underlying biological processes involved.